Uso concomitante de permanganato de potássio no curativo da inserção do cateter venoso central e a prevalência de infecções da corrente sanguínea - Santos, Carlos Eduardo da Rocha [UNESP] (Universidade Estadual Paulista (Unesp), 2017)
As infecções relacionadas à assistência à saúde lideram as causas de morte entre as doenças de notificação obrigatória nos Estados Unidos da América do Norte e são responsáveis por custos elevados, dentre elas, um terço está relacionado às infecções de corrente sanguínea, ocupando a 3a causa de infecções em Unidades de Terapia Intensiva (UTI) e a 10a causa de morte nos EUA. Portanto, a busca de medidas que possam reduzir estas infecções se faz necessária e, neste contexto, a adição de permanganato de potássio ao curativo feito no local de punção venosa central pode ser uma medida eficaz, uma vez que pouco se estuda acerca da técnica do curativo. Em novembro de 2013, este fármaco passou a ser adicionado aos curativos da punção venosa central, na UTI do Hospital Policlin, mantendo-se todas as recomendações do 2011 Guidelines for the Prevention of Intravascular Catheter-Related Infections do Center for Disease Control and Prevention (CDC), isto é, curativo estéril, limpeza com clorexidina 0,5%, e como medida complementar adicionar uma compressa, por 20 minutos, de permanganato de potássio 1:10.000. Assim, a proposta deste estudo foi avaliar a prevalência de infecção de corrente sanguínea, antes e após esta intervenção, nos pacientes internados na UTI do Hospital Policlin 9 de Julho – São José dos Campos – SP. Tratou-se de um estudo de coorte, transversal e retrospectivo, com avaliação do banco de dados de 10.573 cateteres/dia de pacientes internados na UTI do Hospital, que foram divididos em dois grupos, sendo o primeiro composto por 5.273 cateteres/dia no período de 01/06/2011 a 31/10/2013 que não foram submetidos à adição de permanganato de potássio ao curativo do cateter venoso central, e o segundo composto por 5.300 cateteres/dia no período de 01/11/2013 a 30/08/2015, que foram submetidos à adição de permanganato de potássio ao curativo. Foram excluídos do estudo os cateteres/dia dos pacientes transferidos de outras unidades com diagnóstico de infecção; cateteres/dia dos pacientes transferidos de outras unidades que já estavam com cateter venoso central. Para avaliar prevalência de infecção de corrente sanguínea relacionada à utilização de cateter venoso central, foram analisados os dados clínicos que levaram ao diagnóstico de infecção, bem como os resultados das hemoculturas. No grupo de 5.273 cateteres/dia não submetidos à adição de permanganato de potássio ao curativo aconteceram 20 casos de infecção de corrente sanguínea; e no grupo de 5300 cateteres/dia que receberam curativo habitual (2011 Guidelines CDC), submetidos à adição de permanganato de potássio ao curativo do cateter venoso central aconteceram 6 casos de infecção de corrente sanguínea. Os resultados apresentaram significância estatística. Em conclusão, a redução de infecções de corrente sanguínea pela adição do permanganato de potássio 1:10.000 ao curativo habitual (2011 Guidelines CDC) é uma medida efetiva e de baixo custo no gerenciamento e prevenção das infecções de corrente sanguínea em UTI.

Health-care-related infections lead the causes of death among mandatory reporting diseases in the United States and are responsible for high costs, among which onethird is related to bloodstream infections, and is the third leading cause of infection in the United States. Intensive Care Units (ICUs) and the 10th leading cause of death in the United States. Therefore, the search for measures that can reduce these infections is necessary and, in this context, the addition of Potassium Permanganate to the dressing done at the central venous puncture site can be an effective measure, since little is studied about the technique of band Aid. In November 2013, this drug was added to the dressings of the central venipuncture in the ICU of the Policlin Hospital, maintaining all the recommendations of the 2011 Centers for Disease Control and Prevention, I.e., sterile dressing, 0.5% chlorhexidine cleansing, and as a supplementary measure add a pad for 20 min of 1: 10,000 Potassium Permanganate. Thus, the purpose of this study was to evaluate the prevalence of bloodstream infection, before and after this intervention, in patients hospitalized in the ICU of Hospital Policlin 9 de Julho - São José dos Campos - SP. This was a cross-sectional and retrospective cohort study with a database of 10,573 catheters / day of patients hospitalized in the Hospital ICU, divided into two groups, the first consisting of 5,273 catheters / day in the period From 01/06/2011 to 10/31/2013 that were not submitted to the addition of potassium permanganate to the dressing of the central venous catheter, and the second compound for 5,300 catheters / day from 01/11/2013 to 30/08 / 2015, who were submitted to the addition of potassium permanganate to the dressing. The catheters / day of the patients transferred from other units with a diagnosis of infection were excluded from the study; Catheters / day of the patients transferred from other units that already had a central venous catheter. To evaluate the prevalence of bloodstream infection related to the use of central venous catheter, we analyzed the clinical data that led to the diagnosis of infection, as well as the results of blood cultures. In the group of 5,273 catheters / day not submitted to the addition of potassium permanganate to the dressing occurred 20 cases of bloodstream infection; And in the group of 5300 catheters / day who received usual dressing (2011 Guidelines), submitted to the addition of potassium permanganate to the dressing of the central venous catheter, 6 cases of bloodstream infection occurred. The results were statistically significant. In conclusion, the reduction of bloodstream infections by the addition of 1: 10,000 potassium permanganate to the usual dressing (2011 Guidelines CDC) is an effective and low-cost measure in the management and prevention of bloodstream infections in ICU. However, it was a cross-sectional and retrospective cohort study, with an evaluation of the hospital infection control database; And this study design may generate selection bias, so that to confirm our results, it is desirable to initiate a prospective, randomized, blind, placebo-controlled study.
Concomitant use of potassium permanganate at central venous catheter insertion dressing and the prevalence of bloodstream infections
Keywords: Unidade de terapia intensiva; Cateter venoso central; Infecções; Permanganato de potássio; Prevalência de infecção